Sequential traumatisation in the police - Peters-Bean, Kyron M. (Cranfield University, 2000)
There is a paucity of research into traumatic incidents concerning police workers (Hart et al. 1995). There are also few studies relating the prolonged and repetitive exposure to traumatic stressors, or 'sequential trauma' (Gersons and earlier 1990; 1992). Whilst it was acknowledged that organisational stress contributes to adaptive or maladaptive well being, dependent on transactional variables between the person and their environment, it was also argued that further along the stress continuum, there exists gross stress reactions similar to Post Traumatic stress Disorders (PTSD; DSM-IIIR; American Psychiatric Association 1989) and newly revised PTSD criterion (DSM-IV; American Psychiatric Association 1994). However PTSD exclusively relates to a single event of overwhelming magnitude (Davidson and Foa 1991), whilst sequential trauma relates to mUltiple event exposure (Peters-Bean 1990b; 1996). It was argued that the magnitude of stimuli in trauma is not as important as the management of the trauma. Rather trauma is an artefact of person-environment transactions and the operation of 'traumatic signatures' which can be used adaptively or maladaptively in certain scenarios. Models of sequential trauma were proposed and tested. These notions are discussed in relation to three studies: an interview booklet survey (N=89); a Metropolitan Police Survey (N=134) and a Main U.K. Forces Survey (N=528) Results and implications for police workers and further research was discussed. It was found that trauma signatures may possibly assist in the processes involved with encountering trauma, primary and secondary appraisal mechanisms, coping post-event and physiological and psychological well-being with reference to individual and organisational outcomes.